HUBUNGAN ANTARA SELF-EFFICACY SERTA PENGAMBILAN KEPUTUSAN TERHADAP PERILAKU ACADEMIC DISHONESTY PADA MAHASISWA DKI JAKARTA - Brahmantio Saryono, Didik; Kartasasmita, Sandy (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The phenomenon of academic dishonesty remains an important issue in higher education in Indonesia, including in the DKI Jakarta region. This behavior reflects weak academic integrity and can be influenced by various factors, such as self-efficacy and decision-making abilities. This study aims to analyze the relationship between self-efficacy and decision-making in relation to academic dishonesty behavior among university students in DKI Jakarta. This research uses a correlational quantitative approach with 461 participants aged 18 to 25 years. The instruments used include the General Self-Efficacy Scale (GSES), General Decision-Making Style Scale (GDMSS), and Academic Dishonesty Scale (ADS). Data were analyzed using Spearman’s correlation test due to the non-normal distribution of the data. The results show a negative relationship between self-efficacy and academic dishonesty (r = -0.079, p = 0.09), as well as a positive relationship between decision-making and academic dishonesty (r = 0.085, p = 0.068), although both were not statistically significant. Additionally, no gender differences were found in the three variables. These findings emphasize the importance of self-efficacy and decision-making abilities in understanding the tendencies of academic dishonesty behavior, and it is hoped that they will serve as a basis for developing academic integrity improvement programs in higher education. ABSTRAK Fenomena academic dishonesty atau ketidakjujuran akademik masih menjadi isu penting di perguruan tinggi Indonesia, termasuk di wilayah DKI Jakarta. Perilaku ini mencerminkan lemahnya integritas akademik dan dapat dipengaruhi oleh berbagai faktor, seperti self-efficacy serta kemampuan dalam pengambilan keputusan. Penelitian ini bertujuan untuk menganalisis hubungan antara self-efficacy dan pengambilan keputusan terhadap perilaku academic dishonesty pada mahasiswa di DKI Jakarta. Penelitian ini menggunakan pendekatan kuantitatif korelasional dengan jumlah partisipan sebanyak 461 mahasiswa berusia 18 hingga 25 tahun. Instrumen yang digunakan meliputi General Self-Efficacy Scale (GSES), General Decision-Making Style Scale (GDMSS), dan Academic Dishonesty Scale (ADS). Data dianalisis menggunakan uji korelasi Spearman karena data tidak berdistribusi normal. Hasil penelitian menunjukkan adanya hubungan negatif antara self-efficacy dengan academic dishonesty (r = -0.079, p = 0.09), serta hubungan positif antara pengambilan keputusan dengan academic dishonesty (r = 0.085, p = 0.068), meskipun keduanya tidak signifikan secara statistik. Selain itu, tidak ditemukan perbedaan jenis kelamin pada ketiga variabel. Temuan ini menegaskan pentingnya self-efficacy dan kemampuan pengambilan keputusan dalam memahami kecenderungan perilaku academic dishonesty, dan diharapkan dapat menjadi dasar untuk pengembangan program peningkatan integritas akademik di perguruan tinggi.